Fe3O4/N-CNTs derived from hypercrosslinked carbon nanotube as efficient catalyst for ORR in both acid and alkaline electrolytes. (1st June 2022) - Song, Kunpeng; Wei, Jinfeng; Dong, Wen; Zou, Zhijuan; Wang, Jingyu
Abstract: The development of efficient and durable transition metal-based electrocatalysts for the oxygen reduction reaction (ORR) is a key step in the commercial application of renewable energy storage and conversion technology. Herein, a novel and convenient strategy was proposed to embed Fe3 O4 nanoparticles into nitrogen-doped carbon nanotubes (Fe3 O4 /N-CNTs) by the Friedel-Crafts alkylation reaction of iron-tetraphenylporphyrin (FeTPP) and subsequent pyrolysis process. The hypercrosslinked FeTPP framework provided more exposed N and Fe3 O4 active sites on the CNTs surface, and the feasibility to adjust the Fe contents that had a great influence on the composite structure. Moreover, the Fe3 O4 /N-CNTs served as a robust catalyst for the ORR in both acid and alkaline media. Compared with 20% Pt/C, Fe3 O4 /N-CNTs with Fe content of 2.62% exhibited excellent electrochemical performance in terms of positive onset potential ( E 0  = 0.920 V vs. RHE), half-wave potential ( E 1/2  = 0.804 V), much better methanol tolerance, and long-term durability. The remarkable performance of Fe3 O4 /N-CNTs was ascribed to the favorable oxygen adsorption and diffusion, which benefited from its large specific surface area and microporous structure, high reactivity by the exposed graphitic N and oxygen defects, and strong electronic interaction between Fe3 O4 and N-doped CNTs. Highlights: Microporous carbon structure protected the corrosion of CNTs and Fe in electrolyte. Hypercross-linked Fe–N structure increase the stability of Fe3 O4 nanoparticles. Encapsulated Fe3 O4 improve the ratio of defect oxygen.